Effect of ionic conductivity of a PAN-PC-LiClO 4 solid polymeric electrolyte on the performance of a TiO 2 photoelectrochemical cell - Rika; Rahman M.Y.A.; Salleh M.M.; Umar A.A.; Ahmad A. (2023)
A nanoparticle TiO 2 solid-state photoelectrochemical cell has been fabricated. The effect of ionic conductivity of a solid electrolyte of polyacrylonitrile (PAN)-propylene carbonate (PC)-lithium perchlorate (LiClO 4) on the performance of a photoelectrochemical cell of indium tin oxide (ITO)/TiO 2/PAN-PC-LiClO 4/graphite has been investigated. A nanoparticle TiO 2 film was deposited onto ITO-covered glass substrate by controlled hydrolysis technique. A solid electrolyte of PAN-LiClO 4 with PC plasticizer prepared by solution casting technique was used as a redox couple medium. The room temperature conductivity of the electrolyte was determined by AC impedance spectroscopy technique. A graphite electrode was prepared onto a glass slide by electron beam evaporation technique. The device shows a photovoltaic effect under illumination. The short-circuit current density, J sc, and open-circuit voltage, V oc, vary with the conductivity of the electrolyte. The highest J sc of 2.82 ?A cm -2 and V oc of 0.56 V were obtained at the conductivity of 4.210 -4?Scm -1 and at the intensity of 100 mW cm -2. 2010 Springer-Verlag.